Funkcje zasady wzajemnej zgodności we Wspólnej Polityce Rolnej - STANIEWSKA, ANNA (Wydawnictwo Naukowe UAM, 2011)
The subject matter of these considerations concerns functions of the cross compliance within the framework of the Common Agricultural Policy (CAP). References to this prin-ciple are found in many legal acts, both in the first and the second pillar of CAP. The author discusses cross compliance in view of the functions of agriculture. In conclusion the author states among other things that cross compliance does not di-rectly concern the primary function of agriculture, i.e. production of goods to be sold on the market, paid for using market prices or the resulting revenue function, connected with the livelihood of farmers. The basic function of cross compliance is to contribute to the provision of public goods by agriculture. The most important such goods include protec-tion of the natural environment and assurance of food safety. Cross compliance also con-tributes to the creation of public goods of social and recreation nature. An essential func-tion of cross compliance, although not resulting directly from the respective legal regulations, is also to justify the Common Agricultural Policy, both on the international scale and for the European community.

L’oggetto delle considerazioni sono le funzioni del principio di condizionalità (cross- -compliance) nell’ambito della Politica Agricola Comune (PAC). Il riferimento a questo ANNA STANIEWSKA 50 principio si trova in molti atti giuridici, sia nel primo sia nel secondo pilastro della PAC. L’Autrice presenta il principio di condizionalità sullo sfondo delle funzioni dell’agricoltura. In conclusione, l’Autrice afferma, tra l’altro, che il principio di condizionalità non è direttamente correlato né alla funzione di base dell’agricoltura, la quale è la produzione dei prodotti per il mercato, i quali, a loro volta, vengono pagati tramite i prezzi di mercato, né alla funzione rimunerativa, conseguente dalla prima, la quale assicura il sostentamento degli agricoltori. La funzione primaria del principio di condizionalità è di contribuire alla fornitura dei beni pubblici da parte dell’agricoltura. Ai più importanti beni di questo ge-nere appartengono la tutela dell’ambiente e la sicurezza alimentare. Il principio di condi-zionalità contribuisce anche alla nascita dei beni pubblici di carattere socio-ricreativo. Una funzione importante del principio di condizionalità, anche se non derivante direttamente dalla legge, è inoltre il compito di motivare la Politica Agricola Comune sia a livello inter-nazionale sia nei confronti della società europea.